Does Feeding System Influence Parasitism in Black Bengal Goats in Bangladesh? (Progressive Agriculture, 2013)
To study the parasitism in goats in relation to different feeding systems, 1110 goats from different areas of Jaypurhat, Tangail, Netrakona and Mymensingh districts were examined. By fecal sample examination, 76.5% goats were found to be infected with one or more species of endoparasites. In this study, 9 types of helminths ova were identified such as Fasciola gigantica (14.8%), Paramphistomum sp. (28.5%), Schistosoma indicum (3.2%), strongyles (35%), Strongyloides sp. (17.4%), Toxocara spp. (1.5%), Trichuris sp. (4.6%), Capillaria sp. (1.2%) and Moniezia sp. (3.7%). Two types of protozoa were also detected, namely, Eimeria sp. (7.1%) and Balantidium coli (5.5%). Along with these, five species of ectoparasites were found: two species were lice such as Damilinia caprae (13.9 %) and Linognathus vitulli (4.2%), and two species were ticks namely, Haemophysalis bispinosa (21.2%), Rhipicaphalus (Boophilus) microplus (3.6%) and one species was mite, namely, Demodex sp. (2.9%). Mean parasitic burden of Paramphistomum sp. (259.81 ± 3.35) was the highest followed by Eimeria sp. (224.1 ± 16.9) and Moniezia sp. (204.9 ± 19.7). Prevalence of helminths and protozoa was significantly (P